Combination benefit of cognitive rehabilitation plus donepezil for Alzheimer's disease patients. Issue 2 (5th February 2015) - Matsuzono, Kosuke; Hishikawa, Nozomi; Takao, Yoshiki; Wakutani, Yosuke; Yamashita, Toru; Deguchi, Kentaro; Abe, Koji
Abstract : Objects: Alzheimer's disease (AD) is one of the most important diseases in aging society, and non‐drug therapy might be an alternative therapeutic approach. Thus, we evaluated the add‐on effect of cognitive rehabilitation on AD patients under donepezil treatment. Methods: We retrospectively analyzed 55 AD patients with a Mini‐Mental State Examination score of 15–25, dividing them into two groups depending on whether they were receiving ambulatory cognitive rehabilitation (group D + R, n  = 32) or not (group D, n  = 23) in Kurashiki Heisei Hospital over 1 year. The present cognitive rehabilitation included physical therapy, occupational therapy and speech therapy for 1–2 h once or twice a week. Results: Between group D and group D + R, there was no significant difference in baseline data, such as age, Mini‐Mental State Examination score, periventricular hyperintensity on magnetic resonance imaging, deep white matter hyperintensity on magnetic resonance imaging or donepezil dose (4.1 mg/day). At 1 year later, however, the Mini‐Mental State Examination score improved only in group D + R from 21.7 to 24.0 (** P  < 0.001), whereas that of group D remained at 21.5 with both groups of donepezil 5.0 mg/day. Conclusion: The combination of cognitive rehabilitation plus a choline esterase inhibitor donepezil showed a better effect for the cognitive function of AD patients than drug only therapy at 1 year.Geriatr Gerontol Int 2016; 16: 200–204.